Novel optimized link state routing protocol based on quantum genetic strategy for mobile learning. (15th November 2018) - Zhang, De-gan; Zhang, Ting; Dong, Yue; Liu, Xiao-huan; Cui, Yu-ya; Zhao, De-xin
Abstract: In order to support mobile learning, we often use mobile video devices (such as mobile laptop, ipad, mobile phone, mobile TV terminal), mobile audio devices (such as mobile mp3, mobile learning machine), mobile human -computer interaction devices (such as mobile interaction whiteboard, mobile smart space) and so on. The communication of these devices are mainly based on the MANET (Mobile Ad hoc Network). Due to the mobility, self-organization and distributed control of MANET, the routing protocol of MANET has to adapt to the rapid changes of the network structure, and have to make sure the network resources being saved at most. The OLSR (Optimized Link State Routing) is a representative table-driven routing in MANET, and the main technology of OLSR is MPR. In this paper, we improved the quantum genetic strategy, and proposed a new routing protocol named QG-OLSR by combining the characteristics of OLSR. The quick changes of topology of MANET make it a huge challenge to find and maintain an end-to-end optimal path, while heuristic Q-Learning strategy is able to dynamically adjust the routing path through interaction with the surrounding environment. New Q-Learning strategy has been embedded in our improved quantum genetic strategy. The QG-OLSR of this paper optimized the selection of MPR, overcomes the shortage of the traditional protocol, and proves the property of convergence and global optimization. The new routing protocol improved the performance of transmission. The simulation results show that the new protocol is feasible and applicable, and perform a better experimental result.